The Combined Effect of Prostaglandin Administration and Ram Introduction in Multiparous and Nulliparous Sheep in Anestrous Period on Prolificacy - Demiral, Omer Orkun; Abay, Murat; Canooglu, Esra; Ozalp, Gozde Rabia; Risvanli, Ali (Kafkas Univ, Veteriner Fakultesi Dergisi, 2014)
In the study it was aimed to investigate and compare the combined effectiveness of ram introduction (ram effect) and prostaglandin F2 alpha (PGF2 alpha) administration in multiparous and nulliparous Kangal White Karaman ewes during the out of breeding season. The ewes were first divided into two main groups: non-lactating multiparous (Group M, n=104) and nulliparous (Group N, n=101). The multiparous and nulliparous animals were further divided in to two subgroups. Group MRP (n=50 multiparous) and NRP (n=51 nulliparous) were injected with a single dose of PGF2 alpha on the first day of ram introduction. And the Group MR (n=54) and NR (n=50) served as controls with ram introduction but no PGF2 alpha injection. In all of the groups, adult, purebred and fertile rams stayed with the ewes for 45 days. The blood samples were collected at 3-day intervals for 18 days after ram introduction from subsets of ewes (n=17 per group) to monitor the serum progesterone concentration. The total lambing ratios in multiparous and nulliparous animals were 72.1% (75/104) and 44.6% (45/101), respectively (P<0.001). Among the PGF2 alpha and non-PGF2 alpha subgroups of multiparous and nulliparous ewes, the lowest lambing rate was observed in Group NR (36.0%). In multiparous ewes (Groups MR and MRP), the mean progesterone level varied significantly among the days (P<0.001). In contrast, in Group NRP, the progesterone levels varied significantly over the tested time course (P<0.001), but no differences were detected in Group NR (P>0.05). We concluded that being multiparous contributes to the success of PGF2 alpha administration in combination with ram introduction in the anestrous period in ewes. Furthermore, PGF2 alpha administration together with ram introduction positively affects the lambing rate in nulliparous ewes.
Anöstrus dönemindeki multipar ve nullipar koyunlarda koç etkisi ve prostaglandin uygulamalari{dotless}ni{dotless}n dölverimi üzerine kombine etkisi
Keywords: Ram effect; Prostaglandin F2 alpha; Multiparous; Nulliparous Kangal White Karaman; Ewe; Out of breeding season